Coastal and Marine Resources Management Based Local Wisdom at The Haruku Village in Central Maluku District: Pengelolaan Sumberdaya Pesisir dan Laut Berbasis Kearifan Lokal di Negeri Haruku Kabupaten Maluku Tengah - Saiful Gazali; Angela Ruban (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2021)
Local wisdom is a cultural value that cannot be separated from the life of the Maluku people and acknowledged existence. Such as sasi is still a form of local wisdom used as a management guideline and coastal and marine resources management in Haruku villages. Local wisdom (sasi) is a knowledge of natural resource management based on customary systems that have been used for generations by the people of Haruku villages. This research aims to identify the factors that are the reasons for applying sasi in the coastal and marine resources management in Haruku villages. This research uses deep interview methods and structures through questionnaires to provide information about forms of management based on local wisdom. The application of sasi as a coastal and marine resource management system in Haruku villages because sasi has the function of monitoring, supervision, and law enforcement. So, the target for the sustainability of natural resources is maintained and impacts the economic improvement of the community.